Emergence of personality in weaning‐age kittens of the domestic cat?. Issue 5 (10th May 2022) - Urrutia, Andrea; Bánszegi, Oxána; Szenczi, Péter; Hudson, Robyn
Abstract: Individual differences in behavior (animal personality) have recently received much attention although less so in young mammals. We tested 74 preweaning‐age kittens from 16 litters of domestic cats in five everyday contexts repeated three times each across a 3‐week period: a handling test where an experimenter held the kitten, a test where a piece of raw beef was given to the kitten and gradually withdrawn, a test where the kitten was presented with a live mouse in a jar, a test where the kitten was briefly confined in a pet carrier, and an encounter with an unfamiliar human who first remained passive and then attempted to stroke the kitten. We found consistent individual differences in behavior in all tests except with the mouse, although less marked than in equivalent tests with adult cats. Differences in behavior were unrelated to sex, body mass, litter size, or maternal identity. We found only weak correlations in results among the tests (behavioral syndromes), again unlike findings in adult cats. We conclude that weanling kittens show consistent individual differences in behavior but in a different manner to adults. If and how the pattern of such differences changes across development remains to be studied.